Kepemilikan Ambulance Secara Perseorangan - Aitama, Fadia Rozika; Multazam, M. Tanzil (Indonesian Journal Publisher, 2024)
This study aims to find out how the procedures for managing ambulance cars are in accordance with the law, however the law governing the management of individual ambulance car ownership is regulated in DKI Jakarta Governor Regulation number 126 of 2016 ambulance services and corpse cars then in other areas do not have clear rules. The research method used is normative, so it uses systematic and grammatical authentic legal interpretation, then collects facts and then connects them with existing literacy to get general conclusions. The procedure for obtaining an ambulance car ownership permit individually has occurred in an area that wants to apply for an ambulance car ownership permit through the licensing office, which is submitted for follow-up in Surabaya and then continued in DKI Jakarta. legal permission.